Design of Beam Shaping Assemblies for Accelerator-Based BNCT With Multi-Terminals - Li, Guangru; Jiang, Wei; Zhang, Lu; Chen, Weiqiang; Li, Qiang (Frontiers in Public Health, 2021)
To moderate fast neutrons produced by accelerator to appropriate therapeutic energies for boron neutron capture therapy (BNCT), beam shaping assembly (BSA) is required definitely. In this work, based on a model of 2.5 MeV/30 mA proton accelerator, the Monte Carlo simulation software MCNPX was employed to design multi-terminal BSAs. All parameters for both the thermal and epithermal neutron beams at the exit ports of the designed BSAs meet the treatment recommendation values proposed by the International Atomic Energy Agency (IAEA). The clinical parameters of the thermal and epithermal neutron beams were also calculated for clinical indication consideration.